2003
DOI: 10.1029/2001jb001712
|View full text |Cite
|
Sign up to set email alerts
|

Controls on strain localization in a two‐dimensional elastoplastic layer: Insights into size‐frequency scaling of extensional fault populations

Abstract: [1] We use a two-dimensional (2-D) finite element code to investigate how mechanical properties and boundary conditions influence progressive strain localization during extension of a 2-D elastoplastic layer. The deforming medium is modeled using a strain softening Von Mises rheology, with a Gaussian heterogeneity in yield strength distributed randomly in space. Specifically, we examine the effects of changing (1) the thickness of the deforming layer, (2) the basal boundary condition, (3) the range of strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 51 publications
0
31
0
Order By: Relevance
“…The Rift presents high earthquake activity, with several earthquakes of magnitude greater than 6 reported in both historic and instrumental records (Papazachos and Papazachou, 1997). Most of the computed focal mechanisms for both strong events and microearthquakes are in agreement with geodetic data and fault geometry, indicating normal faulting associated with N-S extension Hatzfeld et al, 2000).…”
Section: Geological Settingmentioning
confidence: 55%
See 1 more Smart Citation
“…The Rift presents high earthquake activity, with several earthquakes of magnitude greater than 6 reported in both historic and instrumental records (Papazachos and Papazachou, 1997). Most of the computed focal mechanisms for both strong events and microearthquakes are in agreement with geodetic data and fault geometry, indicating normal faulting associated with N-S extension Hatzfeld et al, 2000).…”
Section: Geological Settingmentioning
confidence: 55%
“…Quaternary geology, geodetic strain rates and the earthquake activity indicate that the currently active Rift zone is confined in the narrow offshore zone of the Gulf of Corinth, extending to the east to the Alkyonides Gulf and the Perachora Peninsula (e.g., Hatzfeld et al, 2000;Briole et al, 2000;Roberts et al, 2009;Leeder et al, 2012) (area covered with faults in red in Fig. 1).…”
Section: Short and Long-term Strain Rates In The Riftmentioning
confidence: 98%
“…These studies indicate that the large volume of relatively undeformed rock located between faults and fault zones contains a rich history of small-scale deformation (Narteau, 2000;Hardacre and Cowie, 2003). This deformation includes small structures that formed early and were later abandoned in favor of other structures that eventually grew to seismic scale features.…”
Section: Apart From Faults and Fault Zonesmentioning
confidence: 99%
“…exponential). In addition, simulations on numerical models [60,69,70] and on analogue laboratory experiments [65,71] showed that the frequency-size distribution depends on the total strain that the fault system has been imposed on and the competition between the different stages of fault growth, i.e. fault nucleation, growth and coalescence.…”
Section: (A) Phenomenology Of Fault and Earthquake Populations (I) Scmentioning
confidence: 99%